2014
DOI: 10.3109/02713683.2014.932388
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparities in Ocular Inflammatory Disorders*

Abstract: Ocular inflammatory disorders disproportionately affect women, and the majority of affected women are of childbearing age. The role of sex or reproductive hormones has been proposed in many other inflammatory or autoimmune disorders, and findings from non-ocular autoimmune diseases suggest a complex interaction between sex hormones, genetic factors and the immune system. However, despite the age and sex bias, factors that influence this disparity are complicated and unclear. This review aims to evaluate the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 141 publications
(156 reference statements)
2
31
0
1
Order By: Relevance
“…Prior studies have shown that ocular inflammatory disorders have a higher incidence in women compared with men, particularly in women of childbearing age, and that this gender difference increases with increasing age [ 17 ]. Sex hormones and the presence of an extra X chromosome in women are thought to play important roles in the development of these immune-mediated diseases [ 17 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have shown that ocular inflammatory disorders have a higher incidence in women compared with men, particularly in women of childbearing age, and that this gender difference increases with increasing age [ 17 ]. Sex hormones and the presence of an extra X chromosome in women are thought to play important roles in the development of these immune-mediated diseases [ 17 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that ocular inflammatory disorders have a higher incidence in women compared with men, particularly in women of childbearing age, and that this gender difference increases with increasing age [ 17 ]. Sex hormones and the presence of an extra X chromosome in women are thought to play important roles in the development of these immune-mediated diseases [ 17 , 35 , 36 ]. While this gender difference has been found in studies performed in several developed countries [ 5 , 6 ], a reverse gender predilection has been noted in developing countries, such as India or Turkey, where a male predominance was found [ 14 , 15 , 19 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Interestingly, 56% of cases are granulomatous and greater than 90% are bilateral. 34, 35 Uveitis, in particular, shows a female predisposition, though it is uncertain whether this is solely because MS is more common in females (upwards of 88% of MS patients with uveitis are female). 31, 34, 35 Idiopathic intermediate uveitis (IU) that often has similar clinical findings of MS is slightly more prevalent in females, with 56% of IU patients being female.…”
Section: Female Predominant Uveitides With Systemic Involvementmentioning
confidence: 99%
“…Sex-based differences in incidence and/or prevalence have been observed in a number of ocular diseases [15]. In particular, those characterized by the aberrant growth of new blood vessels, such as diabetic retinopathy and age-related macular degeneration, have been shown to display a sex bias [6, 7].…”
Section: Introductionmentioning
confidence: 99%